Determining the Effect of Preschool Front the 1st Grade Course Success of Children - Duran, Ayse Açici (CV. Tripe Konsultan, 2025)
Primary school is the education level where academic life begins. The years when the foundations of the future educational life were laid coincide with this period. Thanks to pre-school education, the child develops his autonomy by separating from his family and adopts some basic habits and rules, and will easily adapt to school. It provides a smooth transition for the child to the lesson- and success-oriented education system of primary school. Preliminary learning provided through achievements and activities facilitates the child's success in primary education and provides opportunities for reinforced behavior and learning. Pre-learning has a great impact on children being happy and successful in this environment. The method in the quantitative approach contains a description of the identification of variables; population, sample, and sampling techniques; data collection methods and tools; instrument validation; and data analysis methods. The purpose of this study is about whether pre-school education is effective on first grade students. The purpose of this research is to reveal that there are differences between students who receive pre-school education and those who do not, and to show that students start primary education more prepared and are successful.